Tradisi Akkorontigi dalam Perspektif Hukum Islam (Studi Kasus di Desa Bontosunggu, Kecamatan Bajeng, Kabupaten Gowa) - Syaripudin, Ahmad; Akhmad Hanafi Dain Yunta; Darussalam (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2021)
This study aims to determine and understand the akkkorontigi tradition in the Perspective of Islamic Law and Customary Law that occurred in Bontosunggu Village, Bajeng District, Gowa Regency. This type of writing is field research (field research) using historical approaches, social expectations, anthropological approaches and religious approaches, then data collection methods using interview and observation techniques the author tries to argue about the object being studied in accordance with the reality that occurs in society. The results showed that in carrying out marriage, the akkorontigi tradition is one of a series of wedding processions that cannot be missed and is a habit of their ancestors that has existed since time immemorial. The akkorontigi event is a series of sacred events that are attended by all relatives and invited guests which contain values ​​that are meaningful so that the bride's family can live in harmony. However, in practice, it is necessary to present good intentions and distance oneself from thoughts or beliefs that lead to the shirking of the symbols of tools and objects used in Akkorongtigi. Even so, Akkorongtigi can be preserved by applying several solutions in its implementation, such as wearing clothes that are not tight and covering the genitals, and not shaking hands for non-mahrams.